Examination of nursing theses on oral mucositis in children with cancer in Turkey - Şule Çalışır Kundakçı; Tuğba Öz; Esra Karaca (Termedia Publishing House, 2024)
Oral mucositis is common in children with cancer. Nurses are effective in the management of oral mucositis. For this reason, the study was conducted to examine nursing theses regarding oral mucositis in children with cancer in Turkey. Theses were obtained by scanning the Higher Education Institution National Thesis Centre database. Full text doctoral and master's theses are included. The screening was done with Turkish keywords such as "mucositis", "oral mucositis", and "oral care". Ten theses were included in the study. The majority of the theses in the research (80%) were prepared at the master's level. 60% of the nursing theses related to oral mucositis were made within the Department of Child Health and Diseases Nursing. It was observed that most of the theses (40%) were conducted quasi-experimentally. Nursing theses on oral mucositis in children with cancer were found to be insufficient.